2009
DOI: 10.4236/wsn.2009.14034
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Automatic ECG Diagnosis Method Dedicated to Pervasive Cardiac Care

Abstract: Recent developments of the wireless sensor network will revolutionize the way of remote monitoring in dif-ferent domains such as smart home and smart care, particularly remote cardiac care. Thus, it is challenging to propose an energy efficient technique for automatic ECG diagnosis (AED) to be embedded into the wireless sensor. Due to the high resource requirements, classical AED methods are unsuitable for pervasive cardiac care (PCC) applications. This paper proposes an embedded real-time AED algorithm dedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Incident-recognition-based home healthcare. Some other studies [60] focus on smart home health care, and they use different machine learning based detection techniques to predict sudden events such as sudden heart attacks. Unlike event detection using sound or images, this event detection requires the use of real-time data (such as human state information).…”
Section: Functionality and Security Enhancements Via Learningmentioning
confidence: 99%
“…Incident-recognition-based home healthcare. Some other studies [60] focus on smart home health care, and they use different machine learning based detection techniques to predict sudden events such as sudden heart attacks. Unlike event detection using sound or images, this event detection requires the use of real-time data (such as human state information).…”
Section: Functionality and Security Enhancements Via Learningmentioning
confidence: 99%
“…Apart from wavelet transformation, many other methods were also used in the past twenty years for feature extraction and noise reduction, e.g. geometric analysis [19], difference operation method [20], dynamic threshold [21], spectral analysis [22], Cumulative Sums of Squares [23] etc. Moreover, researchers showed that the neural networks with different configurations were widely used for the classification of ECG signals [24]- [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since interpreting different morphological features [4] of ECG signals helps in predicting or detecting abnormalities in the heart, it is important to know each morphological feature [5], because abnormalities in any of these morphological features signify some underlining heart disease [6]. As most of the real-time systems are embedded in small devices, real time computing deals needs to address constraints in terms of memory, computational power, performance and cost.…”
Section: Introductionmentioning
confidence: 99%